Case studies of U.S. economic sanctions : the Chinese, Cuban, and Iranian experience - Askari, Hossein (Praeger, 2003)
This is the second of three related, empirically based studies examining the broad range of issues raised by the use of economic sanctions. This volume provides a detailed examination of the impact of U.S. economic sanctions on China, Cuba, and Iran as well as the impact on the United States itself.